2015
DOI: 10.5312/wjo.v6.i9.688
|View full text |Cite
|
Sign up to set email alerts
|

Cystic lesion around the hip joint

Abstract: This article presents a narrative review of cystic lesions around the hip and primarily consists of 5 sections: Radiological examination, prevalence, pathogenesis, symptoms, and treatment. Cystic lesions around the hip are usually asymptomatic but may be observed incidentally on imaging examinations, such as computed tomography and magnetic resonance imaging. Some cysts may enlarge because of various pathological factors, such as trauma, osteoarthritis, rheumatoid arthritis, or total hip arthroplasty (THA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 214 publications
0
43
0
3
Order By: Relevance
“…Indeed, Juglard, et al was the first to report in 1991 a case of sciatic nerve compression by a GS. Crawford O, et al has then reported three cases with sciatic nerve compression by a SC in post-operative patients following total hip replacement [1].…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, Juglard, et al was the first to report in 1991 a case of sciatic nerve compression by a GS. Crawford O, et al has then reported three cases with sciatic nerve compression by a SC in post-operative patients following total hip replacement [1].…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
“…Whereas asymptomatic cysts may be followed-up with no medical or surgical intervention, the treatment of cystic lesions of the hip depends on their size, severity of symptoms, nature of the underlying or associated condition, and the presence or absence of the local compression [1]. In fact, an enlarged or painful SC can be treated medically with non-steroidal anti-inflammatory drugs, application of local heat and physical therapy.…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…At MR imaging, the mass appeared to be cystic and communicated with the hip joint, most likely representing a ganglion or synovial cyst (Fig 13b-13d). The differentiation of periarticular cystic lesions of the hip from ganglion or synovial cysts is difficult, as they can have a similar appearance (29).…”
Section: Groin Herniasmentioning
confidence: 99%